Psychometric properties of patient reported outcome measures in idiopathic pulmonary fibrosis. (2nd October 2021) - Kim, Jee Whang; Clark, Allan; Birring, Surinder S; Atkins, Christopher; Whyte, Moira; Wilson, Andrew M
Background: Various patient reported outcome measures (PROMs) are used in idiopathic pulmonary fibrosis (IPF). We aimed to describe their psychometric properties, assess their relationship with 1-year mortality and determine their minimal clinically important differences (MCIDs). Methods: In a prospective multicentre study, participants with IPF completed the King's Brief Interstitial Lung Disease Questionnaire (K-BILD), the modified Medical Research Council (mMRC) dyspnoea scale, St George's Respiratory Questionnaire (SGRQ) and University of California, San Diego shortness of breath questionnaire (UCSD-SOBQ) three-monthly intervals over a 12-month period. Forced vital capacity (FVC) was matched with questionnaires and mortality was captured. Anchor- and distribution-based methods were used to derive MCID. Results: Data were available from 238 participants. All PROMs had good internal consistency and high degree of correlations with other tools (except UCSD-SOBQ correlated poorly with FVC). There were significant associations with mortality for K-BILD (hazard ratio 16.67; 95% CI 2.38–100) and SGRQ (hazard ratio 4.65; 95% CI 1.32–16.62) but not with the other PROMs or FVC. The median MCID (range) for K-BILD was 6.3 (4.1–7.0), SGRQ was 7.0 (3.8–9.6), mMRC was 0.4 (0.1–0.5) and UCSD-SOBQ was 9.6 (4.1–14.2). Conclusions: The K-BILD was related to other severity measures and had the strongest relationship with mortality.